2020
DOI: 10.1016/j.jvscit.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm of external iliac artery after extracorporeal shock wave lithotripsy revealing Behçet disease

Abstract: Extracorporeal shock wave lithotripsy (ESWL) can lead to rare but severe arterial complications. The causal relationship of ESWL with arterial pseudoaneurysm formation in a patient with Behçet disease is discussed. A 35-yearold man presented with acute recrudescence of right flank pain caused by ureteral lithiasis immediately after having undergone a last session of ESWL. Abdominal examination revealed a painful pulsatile mass in the right iliac region. Contrast-enhanced computed tomography identified a pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Iatrogenic procedures, such as percutaneous procedures, renal biopsy, partial nephrectomy, renal transplantation, ESWL, and intrarenal pelvis surgery, are reported as complications. Among the studies on ESWL, one study reported the case of a patient with Behçet’s disease and arterial pseudoaneurysm in the external iliac artery[ 9 ]. Lang et al [ 10 ] reported the case of a patient who developed renal pseudoaneurysm directly after ESWL based on pre- and postprocedural CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic procedures, such as percutaneous procedures, renal biopsy, partial nephrectomy, renal transplantation, ESWL, and intrarenal pelvis surgery, are reported as complications. Among the studies on ESWL, one study reported the case of a patient with Behçet’s disease and arterial pseudoaneurysm in the external iliac artery[ 9 ]. Lang et al [ 10 ] reported the case of a patient who developed renal pseudoaneurysm directly after ESWL based on pre- and postprocedural CT scans.…”
Section: Discussionmentioning
confidence: 99%